PERBANDINGAN MODEL PEMBELAJARAN BERBASIS MASALAH DENGAN MODEL INKUIRI TERBIMBING DALAM PEMBELAJARAN MENULIS KARANGAN NARASI PADA SISWA KELAS VII SMP NEGERI 1 KADUGEDE - Iman (Jurnal Ilmiah Dozen Globalindo, 2021)
The objectives of this study were 1) to determine the learning process of writing narrative essays by applying problem-based learning models and guided inquiry models, 2) to determine student activities in learning to write narrative essays by applying problem-based learning models and guided inquiry models, 3) to determine The problem-based learning model is more effective than the guided inquiry model in learning to write narrative essays, and in class VII SMP Negeri 1 Kadugede. The method used in this research is the experimental method. The population in this study were all grade VII students of SMP Negeri 1 Kadugede Kuningan Regency in the 2015/2016 academic year, totaling 228 students. The sampling technique was cluster random sampling, the authors randomly selected the research sample in order to obtain 2 classes. The sample used in the study was grade VII students. C, totaling 32 students and class VII. E, amounting to 32 students. The data collection technique is a narrative essay writing test. Data processing techniques used are normality test, homogeneity test and hypothesis testing. Based on the calculation of the hypothesis test obtained t hit (6,586)> t list (1.67), so accept Hi means that the problem-based learning model is more effective than the guided inquiry model on the ability to write narrative essays in class VII students of SMPN 1 Kadugede. The conclusions of this study are 1) the learning process of writing narrative essays by applying the problem-based learning model is better than the guided inquiry model, 2) the student activity in learning to write narrative essays by applying the problem-based learning model is better than the guided inquiry model, 3 ) the problem-based learning model is more effective than the guided inquiry model for the ability to write narrative essays.